Boosting thermal regulation of phase change materials in photovoltaic-thermal systems through solid and porous fins - Namuq, Sura A.; Mahdi, Jasim M. (Center of Biomass & Renewable Energy (CBIORE), 2024)
This study explores the integration of porous fins with phase-change materials (PCM) to enhance the thermal regulation of photovoltaic-thermal (PVT) systems. Computational simulations are conducted to evaluate the impacts of different porous fin configurations on PCM melting dynamics, PV cell temperatures, and overall PVT system effectiveness. The results demonstrate that incorporating optimized porous fin arrays into the PCM region can significantly improve heat dissipation away from the PV cells, enabling more effective thermal control. Specifically, the optimized staggered porous fin design reduces the total PCM melting time and decreases peak cell temperatures by about 5°C . This is achieved by creating efficient heat transfer pathways that accelerate the onset of natural convection during the PCM melting process. Further comparisons with traditional solid metallic fins indicate that while solid fins enable 12.2% faster initial melting, they provide inferior long-term temperature regulation capabilities compared to the optimized porous fins. Additionally, inclining the PV module from 0° to 90° orientation can further decrease the total PCM melting time by 13 minutes by harnessing buoyancy-driven convection. Overall, the lightweight porous fin structures create highly efficient heat transfer pathways to passively regulate temperatures in PVT systems, leading to quantifiable improvements in thermal efficiency of 16% and electricity output of 2.9% over PVT systems without fins.